The wellbeing of adolescents and the role of greenness: A cross-sectional study among Italian students - Scaioli, Giacomo; Squillacioti, Giulia; Bersia, Michela; Bellisario, Valeria; Borraccino, Alberto; Bono, Roberto; Dalmasso, Paola; Lemma, Patrizia (Frontiers in Public Health, 2023)
Adolescence is a critical period of life, and the level of well-being acquired during this age might influence the health status in adulthood. Adolescents’ well-being is associated with both biological and environmental determinants. To date, few studies have evaluated the effect of exposure to urban green spaces (i.e., greenness) on adolescents’ well-being. Therefore, the aim of this study was to assess the association between exposure to greenness and adolescents’ well-being, accounting for the urbanization level surrounding schools. In the frame of the Italian Health Behaviour in School-aged Children (HBSC, 2018) study, we analyzed cross-sectional data from the Piedmont Region. Exposure to greenness was quantified by the Normalized Difference Vegetation Index (NDVI). Schools were geocoded, and then a fixed buffer (radius 1500 m) centered on each school was built to allow average NDVI calculations. Adolescents’ well-being was assessed by self-reported psychological, somatic and psychosomatic health complaints as follows. Respondents were asked how often, in the last six months, they had experienced: (a) headache, (b) stomachache, (c) backache, (d) feeling dizziness, (e) feeling low, (f) irritability or bad temper, (g) feeling nervous, and (h) difficulties getting to sleep using the HBSC Symptom Checklist (HBSC-SCL), an eight-item tool. Multivariable multilevel logistic regression models tested the association between exposure to NDVI and psychosomatic, somatic, and psychological health complaints, one at a time and using schools as a random intercept. Overall, 2065 subjects (47.6% females) aged 11 (50.5%) and 13 (49.5%) years were included. Greenness was inversely associated with reported psychosomatic (OR 0.72, 95% CI: 0.53–0.98) and psychological health complaints (OR 0.67, 95% CI: 0.49–0.92) in boys only, adjusting for age, urbanization level, socioeconomic status and stratifying by sex. Our results support the implementation of future policies for urban environmental design supporting the increase in green spaces, as suggested by the United Nations Sustainable Development Goals. Further studies are needed to confirm our findings.